Modern management of perianal fistulas in Crohn's disease: future directions. Issue 6 (13th January 2018) - Kotze, Paulo Gustavo; Shen, Bo; Lightner, Amy; Yamamoto, Takayuki; Spinelli, Antonino; Ghosh, Subrata; Panaccione, Remo
Abstract : Perianal fistulae in patients with Crohn's disease (CD) can be associated with significant morbidity resulting in negative impact on quality of life. The last two decades have seen significant advancements in the management of perianal fistulas in CD, which has evolved into a multidisciplinary approach that includes gastroenterologists, colorectal surgeons, endoscopists and radiologists. Despite the introduction of new medical therapies such as antitumour necrosis factor and novel models of care delivery, the best fistula healing rates reported with combined medical and surgical approaches are approximately 50%. More recently, newer biologics, cell-based therapies as well as novel endoscopic and surgical techniques have been introduced raising new hopes that outcomes can be improved upon. In this review, we describe the modern management and the most recent advances in the management of complex perianal fistulising CD, which will likely impact clinical practice. We will explore optimal use of both older and newer biological agents, as well as new data on cell-based therapies. In addition, new techniques in endoscopic and surgical approaches will be discussed.